Model Strategi Komunikasi Public Relation (Studi Kasus Travelxism pada Program Edu Trava dalam Implementasi Sustainable Tourism di Provinsi Daerah Istimewa Yogyakarta) - Naufal Ryanda Putra; Nora Nailul Amal (Universitas Sebelas Maret (UNS), 2025)
This study aims to analyze the public relations communication strategy model implemented by Travelxism through the Edu Trava program as part of its effort to promote sustainable tourism in the Special Region of Yogyakarta. Edu Trava is an educational initiative that combines training and hands-on field practice, focusing on community empowerment and environmental conservation. Using a descriptive qualitative approach with a case study method, data were collected through in-depth interviews with internal representatives of Travelxism, village tourism partners, and program participants. The findings indicate that the two-way symmetrical communication model is the dominant approach used by Travelxism to build effective relationships with stakeholders, while other models such as public information, publicity, and two-way asymmetrical also play supportive roles. The communication strategies were also analyzed using Hafied Cangara’s five-step communication planning framework, which includes research, planning, implementation, evaluation, and reporting. The results show that program success is not only determined by the message and media used but also by emotional closeness, community engagement, and the sustainability of actions after the program ends. In conclusion, the public relations communication strategy applied by Travelxism through Edu Trava contributes to building a positive destination image, enhancing stakeholder capacity, and strengthening commitment to environmental and social sustainability. These findings can serve as a reference for sustainable communication practices in the tourism sector.